Everyday life after downshifting: Consumption, thrift, and inequality. (29th May 2020) - Lindsay, Jo; Lane, Ruth; Humphery, Kim
Abstract: Much of the early literature on downshifting proposed that reduced hours at work would lead to reduced levels of consumption, increased hours of leisure, and a more sustainable and fulfilling life, and yet recent survey research has challenged these assumptions. Our study contributes knowledge on the differentially lived experience of contemporary downshifting and its relationship to sustainable and/or thrifty consumption. We undertook qualitative interviews with Australians of working age who had voluntarily reduced their hours of work in order to explore the everyday experience of downshifting and its links with consumption practices in the domains of food, leisure, and transport. These downshifters focused on thrift rather than sustainability and consequently did not reduce their consumption in a straightforward way. We found the everyday experience of downshifting was significantly shaped by caring responsibilities and financial and housing security. Moreover, differential levels of financial security affected consumption levels. Although those with lower levels of wealth closely managed discretionary expenditure, financially secure downshifters did not reduce their consumption overall. We argue that reduced working hours are unlikely to lead to reduced consumption in the absence of an ideological commitment to sustainability and without mainstream support for changing consumption mindsets and practices.